Metopa gigas sp. nov. from southern Greenland, a giant among congeners (Crustacea, Amphipoda, Stenothoidae) - Just, Jean (Zootaxa, 2013)
Metopa gigas sp. nov. is described from southern Greenland (east and west). This new species which reaches a length of around 20 mm is, together with M. mirifica Gurjanova, 1948 from the North Pacific, by far the largest member of the ge-nus. The species is easily separated from sympatric Metopa clypeata (Kroyer, 1842; 15 mm; type species of Metopa) with which it has been confused, by small saddle-like ornaments dorsally on pereonites, and much longer antenna 1. It can be distinguished from Metopa mirifica by the simple propodus of gnathopod 1, whereas that of M. mirifica is strongly sub-chelate.